Prevalence of psychiatric morbidity amongst the community dwelling rural older adults in northern India - Tiwari, S.C. (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND & OBJECTIVES: The population of elderly is growing globally and so are the physical illnesses and psychiatric morbidity. This study was planned to assess the prevalence and patterns of psychiatric morbidity amongst rural older adults in Lucknow, north India. METHODS: A survey was conducted in subjects aged 60 yr and above to identify the cases of psychiatric morbidity in rural population from randomly selected two revenue blocks of Lucknow district, Uttar Pradesh, India. All subjects were screened through Hindi Mental Status Examination (HMSE) and Survey Psychiatric Assessment Schedule (SPAS) to identify for the suspected cases of cognitive and the psychiatric disorders, respectively. The subjects screened positive on HMSE and SPAS were assessed in detail on Cambridge Mental Disorder of the Elderly Examination-Revised (CAMDEX-R) and Schedule for Clinical Assessment in Neuropsychiatry (SCAN), to diagnose cognitive disorders and psychiatric disorders (other than the cognitive), respectively on the basis of International Classification of Diseases-10 (ICD-10) diagnostic guidelines. RESULTS: The overall prevalence of psychiatric morbidity in rural older adults was found to be 23.7 per cent (95% CI=21.89-25.53). Mood (affective) disorders were the commonest (7.6%, 95% CI=6.51-8.80), followed by mild cognitive impairment (4.6%, 95% CI=3.72-5.53), mental and behavioural disorders due to substance use (4.0%, 95% CI=3.17-4.87) and dementia (2.8%) [Alzheimer's disease (2.4%, 95% CI=1.81-3.16) and vascular (0.4%, 95% CI=0.16-0.73)]. INTERPRETATION & CONCLUSIONS: Overall prevalence of psychiatric morbidity amongst rural elderly in this study was found to be less in comparison to those reported in earlier studies from India. However, prevalence pattern of different disorders was found to be similar. Therefore, it appears that a stringent methodology, refined case criteria for diagnosis and assessment by trained professionals restrict false diagnosis.